1963
DOI: 10.1002/cber.19630961226
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions‐ und Additionsreaktionen an silylierten Acetylenen

Abstract: Bei Einwirkung von Slurehalogeniden oder -anhydriden auf bis-silylierte Acetylene, wie z. B. Bis-trimethylsilyl-acetylen (I), wird unter Bildung von silylierten Alkinonen nur ein Silylrest durch eine Acylgruppe substituiert. Umsebung von I mit a-Chlor-alkylathern ergibt jedoch durch Substitution beider Silylreste Bisalkoxy-alkine. In mono-silylierten Acetylenen, z. B. im Trimethylsilyl-phenylacetylen, ist die Silylgruppe ebenfalls gegen einen Acylrest austauschbar. Addition von Aziden wie Trimethylsilyl-bzw. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(38 citation statements)
references
References 15 publications
0
36
0
2
Order By: Relevance
“…In contrast, the reaction of benzoyl bromide with hex-3-yne in the presence of 10,20 and 50% of FeCl 3 under the standard reaction conditions afforded a mixture of b-bromo-and b-chloroalkenyl ketones as shown in Scheme 3. These results clearly show that the chloride in FeCl 3 is incorporated in the final product and support the proposed step-wise mechanism in Scheme 2.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, the reaction of benzoyl bromide with hex-3-yne in the presence of 10,20 and 50% of FeCl 3 under the standard reaction conditions afforded a mixture of b-bromo-and b-chloroalkenyl ketones as shown in Scheme 3. These results clearly show that the chloride in FeCl 3 is incorporated in the final product and support the proposed step-wise mechanism in Scheme 2.…”
Section: Resultsmentioning
confidence: 92%
“…2-Fluoro-, 4-fluoro-, 4-bromo-, and 4-chlorobenzoyl chlorides 1f, 1g, 1h and 1l provided 5f, 5g, 5h and 5i on reaction with 2k in 77, 81,79 and 76% yields, respectively (entries [6][7][8][9]. Under similar reaction condition, ortho-, meta-, para-tolyl(trimethylsilyl)acetylenes 2l, 2m and 2n reacted with 1b to to produce 5j, 5k and 5l in 66, 71 and 78% yields, respectively (entries [10][11][12]. Similarly, thiophene-2-carbonyl chloride (1i) gave 5n in 78% yield (entry 14).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…alkyne cycloadditions have been applied. [13] Notably, the TMS-group can lead to a high selectivity considering 4-TMS-triazoles. Initially, a combination of steric interactions and electronic effects, which lead to an increase of the electrophilicity of the b-carbon of alkynes, was assumed.…”
Section: Introductionmentioning
confidence: 99%
“…F or the synthesis of the acetylenik keto ester 4, we found that the acylation of 1-trimethylsily-1-decyne 2b with 3 in the presence of aluminum chloride 9 ) gives a reproducible yield of 70%. The starting silylated acetylene 2b could be obtained readily by silylating the lithium salt of 1-decyne 2a.…”
Section: Tumlinson Et At Have Identified Its Pheromone Isolated Frommentioning
confidence: 93%